2004
DOI: 10.1152/jn.00804.2003
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of a Discontinuity in the Sense of Verticality at Large Body Tilt

Abstract: Interpretation of a discontinuity in the sense of verticality at large body tilt. J Neurophysiol 91: 2205-2214, 2004. First published December 10, 2003 10.1152/jn.00804.2003. Results of earlier spatial-orientation studies focusing on the sense of verticality have emphasized an intriguing paradox. Despite evidence that nearly veridical signals for gravicentric head orientation and egocentric visual stimulus orientation are available, roll-tilted subjects err in the direction of the long body axis when adjustin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
74
1
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(85 citation statements)
references
References 18 publications
8
74
1
1
Order By: Relevance
“…He showed that subjects could accurately adjust themselves to a horizontal position, but, once in this position, made substantial systematic errors in the perception of visual verticality. Later, combined tests confirmed the discrepancy between SVV and SBT accuracy (Mast and Jarchow, 1996;Jarchow and Mast, 1999;Van Beuzekom and Van Gisbergen, 2000;Van Beuzekom et al, 2001;Kaptein and Van Gisbergen, 2004;Vingerhoets et al, 2008). The present study is consistent with these findings, showing substantial systematic SVV errors at tilts Ն60°and fairly accurate SBT performance.…”
Section: Discussionsupporting
confidence: 89%
“…He showed that subjects could accurately adjust themselves to a horizontal position, but, once in this position, made substantial systematic errors in the perception of visual verticality. Later, combined tests confirmed the discrepancy between SVV and SBT accuracy (Mast and Jarchow, 1996;Jarchow and Mast, 1999;Van Beuzekom and Van Gisbergen, 2000;Van Beuzekom et al, 2001;Kaptein and Van Gisbergen, 2004;Vingerhoets et al, 2008). The present study is consistent with these findings, showing substantial systematic SVV errors at tilts Ն60°and fairly accurate SBT performance.…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies have used SVV to investigate the relative contributions of these cue types 12, 13, 14, 15. In the present study, we used not only the SVV but also the SPHV to quantitatively evaluate roll‐tilt perception.…”
Section: Discussionmentioning
confidence: 99%
“…If, for example, subjects are asked to verbally report their estimated roll tilt positions, systematic errors are much smaller than if they are asked to estimate earthverticality (Kaptein and Van Gisbergen 2004;Van Beuzekom and Van Gisbergen 2000;Vingerhoets et al 2008). This suggests that sensory signals of head and body position relative to gravity are processed differently between estimating self-tilt and estimating earth-verticality.…”
Section: Introductionmentioning
confidence: 98%
“…In a recent attempt to better characterize the perception of whole-body orientation, Kaptein and Van Gisbergen (2004) measured self-estimation of body tilt in healthy human subjects who were rotated to various whole-body roll positions over the full range of 360°. These authors found that verbally reported body tilt estimations (using 4 -Tatalias et al…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation